The Urgency of Multicultural Education in Building a Civil Society: The Perspective of Islamic Educational Philosophy - Masduki; Arfanaldy, Sehan Rifky; Pamuncak, Mohammad Bintang; Fahmi (International Journal of Islamic Thought and Humanities, 2025)
Multicultural education is an urgent need in a pluralistic Indonesian society. This article examines the urgency of multicultural education from the perspective of Islamic educational philosophy as a foundation for building a tolerant, just, and inclusive civil society. This study collects and analyzes literature related to multicultural values in Islamic teachings and Islamic educational practices in Indonesia through a qualitative approach with a literature study method. The results of the study show that in the treasury of Islamic educational philosophy, there are fundamental principles that are in line with multicultural values, such as tolerance (tasamuh), justice ('adl), equality (musawah), respect for differences, and the spirit of deliberation (shura). Islam views diversity as part of the sunnatullah that cannot be avoided and must be addressed with mutual respect. However, the reality of Islamic education in Indonesia still shows the dominance of a normative-doctrinal approach, providing little space for cross-cultural dialogue and critical thinking. Therefore, a reconstruction of the paradigm of Islamic education that is inclusive and contextual is needed by instilling multicultural values in the curriculum, learning methods, and educational practices as a whole. Thus, Islamic education does not only function as a transmission of religious knowledge, but also as a tool for social transformation in building a harmonious civil society in diversity. This article highlights explicitly two main questions: (1) how multicultural values are integrated into Islamic educational philosophy, and (2) to what extent such integration contributes to forming a civil society. The main contribution of this study is to offer an integrative conceptual framework that combines Islamic values with the principles of multiculturalism, which can be used as a reference in developing inclusive and contextual Islamic educational policies and practices.